Le Tigre, le Louvre et l’échange de connaissances archéologiques visuelles entre la France et la Grande-Bretagne aux alentours de 1850 - Mirjam Brusius (Les Cahiers de l'École du Louvre)
When in the mid 1850s Assyrian sculptures excavated by a French delegation got lost in the river Tigris all what remained was a set of drawings that the London artist William Boutcher had made during a British expedition in Mesopotamia. In return, the French were in the possession of photographs of fragments from Nineveh that were lost by the British. This essay will re-examine British-Franco relations in the history of archaeology in Mesopotamia against the backdrop of the use and exchange of images, which became the only and major records in a story of rivalry, dependence, loss of objects and control. Not only did objects and images wonder between the two countries, but also new visual recording techniques such as photography, which were not necessarily deployed in the country of their « origin », but across the channel (Manche).